Multidiscipline Applications of Triboelectric Nanogenerators for the Intelligent Era of Internet of Things - Cao, Xiaole; Xiong, Yao; Sun, Jia; Xie, Xiaoyin; Sun, Qijun; Wang, Zhong Lin (Nano-Micro Letters, 2022)
In the era of 5G and the Internet of things (IoTs), various human–computer interaction systems based on the integration of triboelectric nanogenerators (TENGs) and IoTs technologies demonstrate the feasibility of sustainable and self-powered functional systems. The rapid development of intelligent applications of IoTs based on TENGs mainly relies on supplying the harvested mechanical energy from surroundings and implementing active sensing, which have greatly changed the way of human production and daily life. This review mainly introduced the TENG applications in multidiscipline scenarios of IoTs, including smart agriculture, smart industry, smart city, emergency monitoring, and machine learning-assisted artificial intelligence applications. The challenges and future research directions of TENG toward IoTs have also been proposed. The extensive developments and applications of TENG will push forward the IoTs into an energy autonomy fashion. Highlights: 1 Multidiscipline application of triboelectric nanogenerators (TENGs) for intelligent Internet of Things (IoTs) are summarized from the aspects of agriculture, industry, city, emergency monitoring, and artificial intelligence. 2 Perspectives on the challenges and future research directions of TENGs in IoTs have been proposed.